2016
DOI: 10.1080/02699206.2016.1174739
|View full text |Cite
|
Sign up to set email alerts
|

Electropalatographic (EPG) evidence of covert contrasts in disordered speech

Abstract: The phenomenon of covert contrasts has intrigued researchers and clinicians since it was first identified using instrumental data nearly 50 years ago. The term covert contrast refers to phonological contrasts that listeners do not readily identify and which therefore pass unrecorded in transcription-based studies. Covert contrasts are viewed as significant from theoretical and clinical perspectives. Although influential, there are relatively few instrumental studies of covert contrasts. The studies that do exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For further information on the method the reader is referred to Gibbon & Nicolaidis ( [1999]), Ladefoged (: §2.4), Tabain (: §2.1), Harrington (), Murdoch (), Gick et al (: §9.3), and Stone (: §3). A comprehensive bibliography of EPG studies in phonetics and speech language pathology published in English between 1957 to 2013 was compiled by Gibbon (). An online corpus of EPG recordings in the standard video format is made available by the author's lab (Kochetov, Colantoni, & Steele, ), and it currently contains read utterances produced by 25 participants, native speakers of six languages (English, French, Japanese, Korean, Serbian, Spanish, as well as L2 English).…”
Section: Studying Oral Gestures: a Case Studymentioning
confidence: 99%
“…For further information on the method the reader is referred to Gibbon & Nicolaidis ( [1999]), Ladefoged (: §2.4), Tabain (: §2.1), Harrington (), Murdoch (), Gick et al (: §9.3), and Stone (: §3). A comprehensive bibliography of EPG studies in phonetics and speech language pathology published in English between 1957 to 2013 was compiled by Gibbon (). An online corpus of EPG recordings in the standard video format is made available by the author's lab (Kochetov, Colantoni, & Steele, ), and it currently contains read utterances produced by 25 participants, native speakers of six languages (English, French, Japanese, Korean, Serbian, Spanish, as well as L2 English).…”
Section: Studying Oral Gestures: a Case Studymentioning
confidence: 99%
“…Covert contrasts are statistically significant phonetic differences between two sounds, which may be acoustic or articulatory (Gibbon and Lee 2017a), and which, whilst potentially visible on a spectrogram, are not perceivable by the adult native speaker listener or in transcriptions carried out by native speakers (see, for example, Macken and Barton 1980). Child L1 studies on covert contrasts include, for example, the substitution or neutralisation of contrasting sounds, such as sibilant fricatives [s] versus [S] in English or [s] versus [C] in Japanese (Li et al 2008).…”
Section: Covert Contrasts In L1 Acquisition and Adult L2 Acquisitionmentioning
confidence: 99%
“…At the same time, Gibbon and Lee (2017a) note that there is a relative scarcity of research studies and subsequent data to illustrate such contrasts. Gibbon and Lee (2017a) propose that acoustic analysis and other instrumental techniques, such as ultrasound (e.g., Zharkova et al 2017) and electropalatography (e.g., Gibbon and Lee 2017a), may not always capture the existence of a covert contrast due to the complexity (and sheer number) of phonetic cues on which to potentially hone (e.g., Harel et al 2017). It is suggested that incorporating perceptual judgements, whereby listeners judge along a continuous (rather than categorical) scale according to 'target-likeness' or 'prototypicality', may also help to provide evidence of covert contrasts where a measure of acoustic parameters may not (Gibbon and Lee 2017b, p. 2) 11 .…”
Section: Covert Contrasts In L1 Acquisition and Adult L2 Acquisitionmentioning
confidence: 99%
“…Researchers have, therefore, long advocated for instrumentation to support perceptual analyses during the assessment and diagnosis of SSDs. Technological advances and access to instrumentation have developed our understanding of important articulatory distinctions or convert contrasts that are not perceivable to the human ear [ 13 , 14 , 15 ]. McKechnie et al.…”
Section: Introductionmentioning
confidence: 99%